Literary Translation as a Form of Social and Pedagogical Activism - Manolachi, Monica; Musiyiwa, Ambrose (TTR, 2022)
Using the poetry anthology Over Land, Over Sea: Poems for Those Seeking Refuge (Five Leaves Publications, 2015) and Journeys in Translation as case studies, this paper illustrates how literary translation can work as a form of recreation and as social and pedagogical activism. Over the decades, many poetry anthologies focusing on migration have been published around the world. What is new about Over Land, Over Sea is that, unlike similar anthologies, it has been followed by Journeys in Translation, an ongoing, volunteer-driven translation initiative that can be replicated in other contexts. The initiative brings together people from many different countries and backgrounds who are translating the anthology into other languages.